Intelligent Algorithm-Based Methods and Applications for Optimizing Architectural Acoustic Environments: A Reivew - Kotowski, Roman Piotr (Journal of Applied Automation Technologies, 2024)
In the field of architectural acoustics design, traditional optimization methods exhibit significant limitations when addressing complex acoustic challenges. Consequently, intelligent algorithm-based approaches for optimizing architectural acoustic environments have emerged, pioneering new pathways for architectural acoustics design. This paper thoroughly examines the research background and significance of this field, elucidating the practical relevance and potential value of the research topic. Through a comprehensive analysis of the current research landscape, it reveals the primary research content, existing issues, and future research directions. The core contribution of this paper lies in systematically organizing and summarizing the theoretical foundations, application cases, and future development trends of intelligent algorithm-based architectural acoustic environment optimization methods. It provides valuable references and insights for subsequent research, helping to advance the further development and practical application of architectural acoustic environment optimization technologies, thereby enhancing the demand for high-quality architectural acoustic environments.